Autoimmune Thrombotic Thrombocytopenic Purpura, Disseminated Intravascular Coagulation, Haemophagocytic Lympho Histiocytosis—(Following Corona Virus Infection), Fragmented Germ Cells {Liberal Global Abortions, Contraception—(Red Riverways, Blood Moon, Weakened Earth’s Magnet)} and Absence of Abstinence - Samuel, Elizabeth JeyaVardhini; Ramalingam, .; Zumu, .; Aakash, .; Rajmanohar, Celestine; Darmalingam, .; Veerakesari, Sundararajan; Natarajan, S. (Highlights on Medicine and Medical Research Vol. 15, 2021)
Background: Autoimmunity has increased significantly, alarmingly secondary to global contraception, abortion, fragmenting germ cells; herewith three types of life threatening manifestations, are analysed. Case 1: 28 year old afebrile lady, vegetarian, presented to emergency with impaired responsiveness, deep jaundice, menorrhagia of one day duration and she had been taking native treatment with leaves for primary infertility for the past five years; she had a few ecchymotic patches, investigations showed severe anaemia, thrombocytopenia, haemolytic jaundice, peripheral smear confirmed thrombotic thrombocytopenic purpura; she developed profound hematuria; she received treatment with intravenous immunoglobulin, fresh frozen plasma, platelet transfusions, packed red blood cells transfusions, plasmapheresis was planned; she improved gradually. In her sincere effort to conceive a baby, for the past five years, due to cultural ignorance which teaches only three days abstinence, instead of seven days abstinence after last menstrual periods, exposure of germ cells to raw endometrial surface, from 4th to 7th days of menstrual cycle, resulted in the cumulative autoimmunity thrombotic thrombocytopenic purpura status. Case 2: 24 year old lady who had undergone puerperal sterilisation, on the fourth day after last menstrual periods, presented, with unresponsiveness, to emergency, her investigations revealed prolonged prothrombin time, prolonged activated partial thromboplastin time, more than a minute, thrombocytopenia, reduced fibrinogen levels suggesting disseminated intravascular coagulation; her ultra sonogram abdomen showed, absence of gestational sac in the uterus; she received fresh frozen plasma transfusions, but succumbed within few hours. With puerperal sterilisation, [non evidence based medical practice], 20 million germ cells are fragmented to chromatid breaks, acentric fragments, ring chromosomes, which get exposed to partly regenerated endometrial surface, on the fourth day after last menstrual periods, due to lack of awareness of abstinence upto seven days, initiating severe cumulative autoimmunity, resulting in fatal disseminated intravascular coagulation. Case 3: Fatal haemo-phagocytic lympho-histiocytosis soaring autoimmunity, detected in the victim host of corona virus infection, correlated directly with extensive tissue damage produced in the victim host, by prior surgical abortions. Conclusion: Cases one and two followed absence of abstinence, with exposure of germ cells, to partly healed endometrial surface in the former culminating in thrombotic thrombocytopenic purpura; in the latter by exposure of fragmented 20 million germ cells [by contraception] to partly healed endometrial surface, culminating in fatal disseminated intravascular coagulation. In case three fatal autoimmune hemo-phagocytic lympho-histiocytosis followed corona virus infection, secondary to extensive tissue damage, of liberal global abortions. Red Russian riverways, is another evidence for global warming due to global aborted blood pollution, melting Perma Frost crashing the Diesel tanks, with oil spill reflecting on aborted blood polluted river, turns bright red, similar to blood moon by abortion polluted air. Innumerable human lives with their iron of blood flowing within blood vessels, repelling magnet of earth, is mandatory to strengthen earth’s magnet. Arctic ozone hole closed this May, environmental pollution cleared, by absence of global abortions, contraception, and their ozone depleting blood pollution, due to lock down of corona virus pandemic.